The design of the cost system in government units and its role - Hussein, Rand Sabah (Opción, 2020)
In order to improve the cost system, different techniques have been adopted in PSO‟s (public sector organizations) such as Performance and Program Costing System (PPCS), Performance Based Costing System (PBBS) and Zero-Based Costing (ZBC). The current study attempts to extend this line of reasoning as little research had been conducted in underdeveloped countries regarding implementation of “One Budgetary Approach” .The findings are a fair familiarity and understanding of PPCS by financial managers and accountants following the accounting system by “public sector organizations” contributes to adopt PPCS successfully, enjoy certain benefits with adopting PPCS, and along with, certain obstacles have been explored.